OPPORTUNITIES FOR ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING IN THE FIELD OF ENGINEERING GRAPHICS - Mashrapova Gulbakhor Mamasaliyevna (Modern American Journals, 2025)
This article examines the current opportunities and future potential of artificial intelligence and machine learning in the field of engineering graphics. Drawing on a review of recent literature, comparative analysis of AI-enhanced CAD platforms, and expert interviews from academia and industry, the study highlights the significant benefits achieved through the automation of design tasks, reduction of drafting errors, and the enhancement of engineering education via intelligent tutoring systems. Key findings demonstrate measurable improvements in productivity, accuracy, and creativity, though challenges remain related to skills development, integration costs, and the need for trustworthy, transparent AI. The article concludes that AI and machine learning are set to play a pivotal role in the ongoing digital transformation of engineering graphics, with broad implications for industry, education, and policy.
Keywords: Engineering graphics; artificial intelligence; machine learning; CAD; generative design; intelligent tutoring systems; automation; digital transformation; engineering education; design optimization.